Manufaktur Sampan (Canoe) Dengan Bahan Paduan Aluminium untuk Wisata Sungai - Wisnujati, Andika; Mudjijana, Mudjijana; Octantha, Esron Fernando (Berdikari: Jurnal Inovasi dan Penerapan Ipteks, 2016)
Specific objectives and targets to be achieved are the new business entrepreneurs in the field of manufacture of canoes (canoe) for water vehicles, especially in the river Winongo and generally in places of tourism in other areas. This new entrepreneur will be made in Kampung Pojok, Sinduadi Urban Village, Mlati Sub-district, Sleman Re-gency, DIY (Winongo west side bank). Canoe manufacturing starts from the design (design) of construction which in this case ask for help 4 students of Mechanical Engineering Department and Industrial Faculty of Engineering UGM. Based on the design drawings can be calculated the amount of aluminum alloy material in the form of a 2 thick plate and pipe Â¾ inch for the construction of the amplifier. The cutting of the plate is carried out with the betel in accordance with the drawing (the initial stage) and smoothed with hand grinding prior to connection with the electric welding with aluminum alloy electrodes. Similarly, the reinforcing and buoying rods are sawn with a hand saw (initial stage) and connected with an electric weld. In the end the product is tested in the flow of Winongo River, near the canoe production place in the village of Pojok, Sinduadi, Mlati, Sleman. Canoe products are tested by students of the Yogyakarta Maritime Academy. Test results should show no leakage in each canoe connection when in use and on reliable stability conditions.Â Keywords: Canoe, Water Vehicle, Winongo River, Reliable, Aluminium